Reproductive health self-care for female students: Educational needs assessment, Isfahan University of Medical Sciences 2018 - Maryam Hashemi; Shahnaz Kohan; Mahshid Abdishahshahani (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Young people play major roles in the future of a society and face major challenges in the field of reproductive health during this period. Therefore, it is particularly important to investigate their educational needs for the reproductive health self-care. AIMS: The present study aimed to provide a needs assessment and determine the educational needs of reproductive health self-care in female students. SETTINGS AND DESIGN: Isfahan University of Medical Sciences. The present research was descriptive cross-sectional. SUBJECTS AND METHODS: Data were collected from 96 female students who were selected using quota sampling and also 15 providers of reproductive health services. Data collection tool was a researcher-made questionnaire comprising two parts of the demographic information and the reproductive health needs assessment. The content and face validity were determined by the cooperation of ten reproductive health and adolescence health experts, and Cronbach's alpha coefficient was used to determine the reliability of the questionnaires. STATISTICAL ANALYSIS USED: Data analysis was done by descriptive statistics (mean and frequency distribution) and one-sample t-test using the SPSS 20 version. RESULTS: The total mean of needs for reproductive health education was 3.51 out of 5 in female students. Apart from the high-risk behavior, mean scores of other fields were significantly greater than the average (3). Three educational priorities included cervical cancer, violence against women, and ovarian cysts. In addition, among the popular educational methods, most people chose the non-attendance method and mostly mobile applications and then educational booklets. CONCLUSIONS: Results indicated that female students had a great need for self-care education in different fields of reproductive health; hence, it seems essential to implement the educational programs in accordance with their needs by taking advantage of the available learning opportunities in universities, particularly universities of medical sciences for their health promotion and empowerment to acquire self-care skills. Furthermore, the present research emphasized the need to pay attention to education using the Internet applications.